Pengaruh Keadilan Kompensasi Pada Kepuasan Kerja Karyawan Di Bank Perkreditan Rakyat - Dedi Setiawan (Universitas Muhammadiyah Yogyakarta, 2016)
In this thesis examines the effects of equity compensation to employee satisfaction at rural banks in four-dimensional jogjakarta.keadilan compensation includes distributive justice, procedural justice, interpersonal justice and informational justice. pembhasan two-dimensional distributive justice and procedural fairness emphasis on formal aspects of managerial, and two-dimensional interpersonal information justice emphasizes the social aspect.Samples are used as much as 6 rural banks, rural banks based 3 conventional and 3-based sharia rural banks. with the object of research is as much as 175 employees RB respondents.Results showed that of the four variables: distributive justice, procedural justice, interpersonal justice, fairness infoemasional, expressed significantly influence employee satisfaction.